Cytokine Storm as a Cellular Response to dsDNA Breaks: A New Proposal - Shabrish, Snehal; Mittra, Indraneel (Frontiers in Immunology, 2021)
Pathogenesis of cytokine storm is poorly understood. In this article we propose a new mechanism and suggest innovative therapeutic avenues for its prevention. We have reported that particles of cell-free chromatin (cfCh) that are released from the billions of cells that die in the body everyday can illegitimately integrate into genomes of healthy cells to trigger dsDNA breaks. The latter leads to apoptosis and / or intense activation of inflammatory cytokines in the affected cells. We hypothesise that a similar phenomenon of dsDNA breaks and inflammation is involved in cytokine storm. The abundant cfCh particles that are released from dying host cells following viral / microbial invasion initiate a cascading effect of more cell death to initiate a vicious cycle of further DNA damage, apoptosis and hyper-inflammation which culminate in cytokine storm. We propose that this unrelenting vicious cycle of cellular DNA damage and cytokine storm may be the underlying cause of high mortality from severe COVID-19. We discuss results of our preclinical studies wherein we have shown that endotoxin induced cytokine storm in mice can be reversed by three different agents that have the ability to inactivate cfCh. These agents may be worthy of investigation in clinical trials to reduce mortality from COVID-19.